Dual band inverted L‐shape monopole antenna for cellular phone applications. Issue 12 (December 2014) - Sambhe, Vijay K.; Awale, R. N.; Wagh, Abhay
ABSTRACT To mitigate the requirement of dual band cellular phone applications, inverted L‐shaped monopole antenna is proposed in this article. The proposed antenna have optimum dimensions 22 (L) × 76 (W) × 1.6 (h) mm3 and fabricated on easily available FR4 substrate with permittivity 4.4 and loss tangent is 0.02. The structure is feed to 50‐Ω microstrip line and terminated with SMA connector. The antenna covers 824–894 MHz (AMPS), 890–960 MHz (GSM) in lower frequency bands, and 2–2.5 GHz (Wi‐Fi, Bluetooth, WiMAX) in upper frequency bands. Measured VSWR is ≤2 for both dual band of frequencies. The antenna shows acceptable gain flatness from 1.5 to 3.59 dBi with good omnidirectional radiation pattern. In addition, an attempt is made to investigate the effect of L‐patch on the impedance bandwidth with extensive simulation and result are presented. The antenna offers high efficiency for both dual frequency bands and easy integration with the other microwave circuits. Its simplicity, gain flatness, and radiation patterns make it suitable for dual band cellular phone applications. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2751–2755, 2014